COVID-19 Flow-Maps an open geographic information system on COVID-19 and human mobility for Spain - Miguel Ponce-de-Leon (Nature Portfolio, 2021)
Measurement(s) COVID-19 cases • mobility • population Technology Type(s) Real Time PCR • mobile phone Sample Characteristic - Organism Homo sapiens • Severe acute respiratory syndrome-related coronavirus Sample Characteristic - Location Kingdom of Spain Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.15198123